Ringer - Oliver, Lauren, 1982- (Harper, an imprint of HarperCollinsPublishers, 2017)
In a book that invites readers to start at either end or alternate between perspectives, Lyra and Caelum struggle in the world outside of the Haven Institute, while Gemma and her boyfriend Pete try to stop her father's plans for the replicas, but are mistaken for escapees and brought to a secret facility.